2005
DOI: 10.1017/s0031182004006614
|View full text |Cite
|
Sign up to set email alerts
|

High levels of congenital transmission of Toxoplasma gondii in longitudinal and cross-sectional studies on sheep farms provides evidence of vertical transmission in ovine hosts

Abstract: Recent research suggests that vertical transmission may play an important role in sustaining Toxoplasma gondii infection in some species. We report here that congenital transmission occurs at consistently high levels in pedigree Charollais and outbred sheep flocks sampled over a 3-year period. Overall rates of transmission per pregnancy determined by PCR based diagnosis, were consistent over time in a commercial sheep flock (69 %) and in sympatric (60 %) and allopatric (41 %) populations of Charollais sheep. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 29 publications
2
75
1
6
Order By: Relevance
“…Chronic T. gondii infections in ruminant dams may cause abortion by reactivation of the parasite during pregnancy [5]. Although most infections in humans are asymptomatic, abortion may also occur after congenital T. gondii infection [3].…”
mentioning
confidence: 99%
“…Chronic T. gondii infections in ruminant dams may cause abortion by reactivation of the parasite during pregnancy [5]. Although most infections in humans are asymptomatic, abortion may also occur after congenital T. gondii infection [3].…”
mentioning
confidence: 99%
“…Further recent studies on sheep have revealed that congenital transmission may be sufficient to explain the maintenance of T. gondii in natural populations of sheep without requiring new infections by oocysts secreted by cats. [22][23][24][25] In the case of these sheep studies, it was demonstrated that PCR detection of T. gondii DNA in the umbilical cord was a good indicator of infection when aborted lamb brain tissue was compared in the same animal. Nevertheless, a challenge to be encountered in humans (as may be the case in sheep and other animals) is to understand whether these individuals are truly asymptomatic carriers of vertical transmission.…”
Section: Discussionmentioning
confidence: 99%
“…22 Appropriate protocols were used at each stage of the DNA purification and any subsequent PCR amplifications to prevent cross-contamination as described previously. 21,23,25,35 PCR detection of T. gondii Detection of T. gondii was carried out using a nested PCR amplification of both surface antigen gene 1 (sag 1) as described previously 24,36 and surface antigen gene 3 (sag 3) 37 with subsequent modifications. 38 Pure T. gondii DNA from RH, Martin, 17695 and COR strains were used as positive controls in all PCR experiments.…”
Section: Sample Collection and Ethical Approvalmentioning
confidence: 99%
See 2 more Smart Citations